Communication (Surgery in East Africa - Technology and Training) - Wood, Michael Dr (My University, 1981)
Perhaps our most disturbing deficiency is nor our lack of knowledge but our inability to use the knowledge we have (Bryant 1969). Introduction The situation quoted above may be a key to an understanding of the health predicament in developing countries. We do not apply the knowledge we have because in many instances we cannot reach the people who require it. The term communications covers many different concepts, but my brief today is to consider the urgent business of getting to the patient and some ways of overcoming the problems of distance and isolation.
Keywords: Communications; Surgery; Knowledge; Radio; Aeorplanes; Land Rover